Errata: Communications – Scientific Letters of the University of Zilina, Vol. 20, No. 3, 2018, „Electrochemical Characterization of Az31 Magnesium Alloy Treated by Ultrasonic Impact Peening (Uip)“, pp. 24-29. The proper Acknowledgement should be as follow - Daniel Kajanek; Branislav Hadzima; Filip Pastorek (Communications - Scientific letters of the University of Zilina, 2019)
Errata: Communications – Scientific Letters of the University of Zilina, Vol. 20, No. 3, 2018, „Electrochemical Characterization of Az31 Magnesium Alloy Treated by Ultrasonic Impact Peening (Uip)“, pp. 24-29. The proper Acknowledgement should be as follows:The research was supported by project ITMS 26220220048 and by Slovak Research and Development Agency by the project No. APVV-14-0772.